Parametric Characteristics of Conflict of Interests between Owners and Managers in Corporations - BONDARENKO, Irina Alekseevna; VANDINA, Olga Georgievna; RUSETSKAYA, Elvira Antsasovna; CHARAKHCHYAN, Konstantin Karenovich (Journal of Advanced Research in Law and Economics, 2017)
Institutional analysis of the essence of the corporate conflict from the standpoint of its structure and composition of its participants made it possible to proceed to a new paradigm of the correlation of the characteristics of the given conflict: parametric and nonparametric. The novelty of distinguishing the ‘parametric characteristics’ of the conflict of interests is that methodologically this technique allows us to separate the personal and professional interests of owners – managers and shareholders-owners; these interests contradict each other and are realized only to the detriment of one of them. Thus, parametric characteristics enable management to ‘split’ these interests at different levels of corporate governance, giving opportunity to realize them in some cases and depriving such an opportunity in other cases. In this regard, there is a problem that has not been resolved in Russian corporate law for a long time: the role of the audit commission as an internal control body. The conflict of interests between owners and managers and the ways of its resolution are of particular relevance in the conditions of need for a systematic improvement of efficiency of corporate governance. The article is devoted to study of the nature of aggregate corporate conflicts in terms of preventing or mitigating them at least